Predicting Thermal Comfort of HVAC Building Using 6 Thermal Factors - Mohamed Salleh F.H.; Saripuddin M.B.; Bin Omar R. (Institute of Electrical and Electronics Engineers Inc., 2023)
Barium compounds; Forecasting; Nearest neighbor search; Office buildings; Sodium compounds; Support vector machines; Thermal comfort; Accurate prediction; Classification trees; Commercial building; Environmental conditions; K-nearest neighbors; Machine learning models; Prediction process; Thermal factors; HVAC